2009
DOI: 10.1007/s11538-009-9399-5
|View full text |Cite
|
Sign up to set email alerts
|

Front Instabilities and Invasiveness of Simulated Avascular Tumors

Abstract: We study the interface morphology of a 2D simulation of an avascular tumor composed of identical cells growing in an homogeneous healthy tissue matrix (TM), in order to understand the origin of the morphological changes often observed during real tumor growth. We use the GlazierGranerHogeweg model, which treats tumor cells as extended, deformable objects, to study the effects of two parameters: a dimensionless diffusion-limitation parameter defined as the ratio of the tumor consumption rate to the substrate tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 133 publications
8
84
0
3
Order By: Relevance
“…For e ¼ 0, i.e., no attraction between cells, T ¼ 0 and the tumor front is always stable as found in the long-wavelength limit and various tumor models [17,26]. In the more realistic radial case, a necrotic core develops quickly, all the proliferative activity being confined in a ring of quasiconstant width l with a radius RðtÞ growing linearly in time (dR=dt ¼ _ R ¼ U) as observed in vivo [16] [ Fig.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 72%
“…For e ¼ 0, i.e., no attraction between cells, T ¼ 0 and the tumor front is always stable as found in the long-wavelength limit and various tumor models [17,26]. In the more realistic radial case, a necrotic core develops quickly, all the proliferative activity being confined in a ring of quasiconstant width l with a radius RðtÞ growing linearly in time (dR=dt ¼ _ R ¼ U) as observed in vivo [16] [ Fig.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 72%
“…Direct representations of adhesion were first considered in the context of individual cell-based models (Turner & Sherratt 2002;Turner et al 2004;Grygierzec et al 2004). In recent years, this modelling approach has been developed significantly by Anderson and coworkers, in a series of sophisticated studies into the ways in which changes in cell-cell and cell-5 A c c e p t e d m a n u s c r i p t matrix adhesion interact with other aspects of the invasive phenotype (Anderson et al 2006Ramis-Conde et al 2008;Poplawski et al 2009). …”
Section: Modelling Adhesion In Invasion Processesmentioning
confidence: 99%
“…For nutrient-poor tumor growth, increasing adhesion can limit the rate of tumor fragmentation and the extent of tissue invasion [17]. Morphological instabilities were observed for nutrient-poor tumor growth, with the degree of instability increasing greatly with decreasing surface tension [23]. The fingering tumor cell population generally have low cell adhesion and oxygen consumption rates [32] and are observed for a combination of the strength of cell-cell adhesion and haptotaxis [33].…”
Section: Chemotaxis and Surface-tension In A Nutrient-poor Microenvirmentioning
confidence: 99%
“…Instability provides a mechanism for tumor invasion that does not require development of a neovasculature to supply essential nutrients. Poplawski et al [23,24] demonstrated that the development of instability depends primarily on the diffusional limitation parameter (ratio of tumor growth rate to diffusion rate of nutrients) while the morphological details depend on cell-cell adhesion. The lack of competition for nutrients (high nutrient environment) promotes spherical, noninvasive tumors.…”
Section: Introductionmentioning
confidence: 99%